A new approach to energy consumption per capita stationarity: Evidence from OECD countries - Ozcan, Burcu; Ozturk, Ilhan (Pergamon-Elsevier Science Ltd, 2016)
Applying a new panel stationary test procedure to data from 32 OECD countries from 1971 to 2013, this study examines the time series properties of per capita energy consumption. The results indicate that energy consumption per capita follows a mean reverting process for 16 OECD countries whereas, for the remaining 16 OECD countries, a mean reverting process is not the case. Besides, energy consumption per capita exhibits some sharp and smooth structural shifts (breaks) in its mean and/or trend levels, and the endogenously identified break dates correspond to specific macroeconomic events such as oil crises, Gulf War, Asian and Global financial crises. These results also have important policy implications. For the 16 OECD countries that have stationary energy consumption per capita series, government policies intended to stabilize energy demand will have no long-lasting effects, and therefore, governments should not adopt unnecessary policy targets for energy demand level. However, for the remaining 16 OECD countries, such policies will have long-lasting effects. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Energy consumption; Unit root test; Stationarity; OECD